Stress distribution of three-unit fixed partial prostheses (conventional and pontic) supported by three or two implants: 3D finite element analysis of ductile materials. Issue 7 (19th May 2019) - Toniollo, Marcelo Bighetti; Vieira, Ligia Jaqueline Pereira; dos Santos Sá, Mikaelly; Macedo, Ana Paula; Melo, Jair Pereira de; Terada, Andrea Sayuri Silveira Dias
Abstract: In implantology, when financial or biological feasibility limitations appear, it is necessary to use prostheses with geometries that deviate from the conventional, with a pontic in the absence of an intermediate implant. The aim of this study was analyze and understand the general differences in the stresses generated in implants, components and infrastructures according to the configuration of the prosthesis over three or two implants. Thus, this paper analyzes the von Mises equivalent stresses (VMES) of ductile materials on their external surfaces. The experimental groups: Regular Splinted Conventional Group (RCG), which had conventional infrastructures on 3 regular-length Morse taper implants (4x11 mm); Regular Splinted Pontic Group (RPG), which had infrastructures with intermediate pontics on 2 regular-length Morse taper implants (4x11 mm). The simulations of the groups were created with Ansys Workbench 10.0 software. The results revealed that the RPG presented greater areas of possible fragility due to higher stress concentrations, for example, in the cervical area of the union between the implant and component the top platform of the abutment, as well as greater coverage of the stress by the cervical implant threads. The RPG infrastructure was also more affected by stresses in the connection areas between the prostheses and on the occlusal surface. There is an advantage to using prostheses supported by a greater number of implants (RCG) because this decreases the stress in the analyzed structures and consequently improves stress dissipation to the supporting bone, which would preserve the system.